2018
DOI: 10.1111/ijfs.13934
|View full text |Cite
|
Sign up to set email alerts
|

Towards improving the nutrition and health of the aged: the role of sprouted grains and encapsulation of bioactive compounds in functional bread – a review

Abstract: Aging reduces the absorption of nutrients. Literature related to functional bread processing techniques including sprouting of grains and the application of encapsulation technology and the bioavailability of bioactives was reviewed. Functional ingredients including sprouted/germinated grain particularly brown rice and wheat flours enhance the bioactive properties of functional bread. Ingredients with high polyphenol content such as lavender and melissa by-products, tea-extracts and aronia powder enhance the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 94 publications
0
17
0
2
Order By: Relevance
“…However, the inclusion of pomegranate decreased in mineral bioavailability. Functional bread and bakery products enhanced with bioactive compounds could help in fortification strategies of the elderly and help to enhance the absorption of nutrients (Amoah et al ., ). Lesinski et al .…”
Section: Baked Goods As Functional Foodsmentioning
confidence: 97%
“…However, the inclusion of pomegranate decreased in mineral bioavailability. Functional bread and bakery products enhanced with bioactive compounds could help in fortification strategies of the elderly and help to enhance the absorption of nutrients (Amoah et al ., ). Lesinski et al .…”
Section: Baked Goods As Functional Foodsmentioning
confidence: 97%
“…The challenge is that bread with high moisture content is susceptible to microbial growth, especially moulds [88]. Nevertheless, we have reported that, bread enriched with functional ingredients, tend to have a longer shelf-life than bread formulated from refined wheat flour [89]. This is due to the reduced oxidation of lipids and protein by the bioactives present inherently in the functional ingredients and the bioactives acting as antimicrobial agents against the growth of mould [89].…”
Section: Fruit and Vegetable By-product Valorization In Functional Breadmentioning
confidence: 99%
“…Nevertheless, we have reported that, bread enriched with functional ingredients, tend to have a longer shelf-life than bread formulated from refined wheat flour [89]. This is due to the reduced oxidation of lipids and protein by the bioactives present inherently in the functional ingredients and the bioactives acting as antimicrobial agents against the growth of mould [89]. Broccoli by-products from the stem and leaves were incorporated into bread and its impact on bread qualities evaluated [6].…”
Section: Fruit and Vegetable By-product Valorization In Functional Breadmentioning
confidence: 99%
“…Amoah et al . reviewed the developments in functional bread processing techniques. Globally, bread is an important food source and many opportunities to enhance the functional properties of this category are presented.…”
mentioning
confidence: 99%
“…Globally, bread is an important food source and many opportunities to enhance the functional properties of this category are presented. The use of techniques such as incorporation of beneficial bioactive compounds by encapsulation techniques has shown a favourable effect on the shelf‐life of the product and increased antioxidant status of consumers (Amoah, Cairncross et al . 2019).…”
mentioning
confidence: 99%